Three Cheetah, One Guide, and the Setting Sun: Magic on McKenzies Koppie - Milton, Martin (The Trumpeter, 2019)
An encounter with cheetah on the plains of Botswana is described and used to consider the experience of being-in-the-(natural)-world. The importance of contact with nature is discussed alongside some of the issues we face both personally and globally.